Alocação de áreas florestadas visando a conservação do solo e da água em propriedades familiares - Zarnott, Daiane Hellnvig (2012)
A growing concern over environmental problems is becoming increasingly present in everyday population. The intensive use of land mainly for agriculture and the exploitation of water resources for various purposes, are producing environmental impacts which result in economic losses to society. In rural areas, many of these impacts are related to production and transportation of sediments, showing the importance of identifying the main areas of occurrence of these processes in watersheds. The use of tools for the prediction of soil loss is of great value for planning and management of water resources in a region. This study aimed to identify the areas with the greatest potential for soil loss in a rural watershed with predominant occurrence of properties with family-based production, draw a map of sediment yield and simulate the allocation of forest cover (preferably native forest), to reduce the soil loss potential through geoprocessing tools and remote sensing. The work was conducted in the watershed of the Sinnott Water Treatment Plant (Pelotas, Brazil), which has an area of approximately 69,600 hectares. To identify locations with higher soil loss potential it was applied the MUSLE (Modified Universal Soil Loss Equation), considering the scenario of current soil use. Afterward two simulations were performed, considering different scenarios of forest cover: simulation 1, with forested areas covering 30 meters surrounding the watercourses, and simulation 2, with forested areas covering land with slopes greater than 20%. The results indicate that the greatest soil loss potential occurred where there were areas with higher human action and higher slopes. For the simulated scenarios relating to forested areas, the simulation 2 showed the greatest reduction of soil loss potential, indicating that protection against water erosion in the study area would present better results when forested areas were allocated to regions with higher slopes. The use of the MUSLE model, together with GIS tools and remote sensing for the simulation of soil loss, has proved to be feasible for the delimitation of areas with high erosion risk.